2020
DOI: 10.21203/rs.3.rs-95498/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Dengue Prediction Through Machine Learning and Deep Learning: A Scoping Review Protocol.

Abstract: Background: Dengue is an endemic disease caused by the DENV virus. There are four types of serology for this virus (DENV1, DENV2, DENV3 e DENV4). All of these variations can cause the disease and, once infected with one type, the patient is not immune against other serologies. Due to the particularity of the virus serology, as well as the ease of reproduction of the transmitting mosquito, approximately 4.3 million people suffered from this disease in 2019. Although it is not a new disease, there is still no ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…Batista et al confirmed superiority with ML techniques demonstrating a lower error rate compared to the conventional statistics-based model in predicting dengue cases. In the age of big data, this technique can leverage data availability and in addition to being non-parametric in nature, can also provide some leeway in terms of strict assumption [86]. Random forest, neural networks, gradient boosting and support vector algorithms are notable subsets of machine learning algorithms, which have made significant contributions to several areas of public health, particularly in the forecasting of infectious diseases like malaria [87] and COVID-19 [88], and may have similar utility for making dengue outbreak predictions.…”
Section: Discussionmentioning
confidence: 99%
“…Batista et al confirmed superiority with ML techniques demonstrating a lower error rate compared to the conventional statistics-based model in predicting dengue cases. In the age of big data, this technique can leverage data availability and in addition to being non-parametric in nature, can also provide some leeway in terms of strict assumption [86]. Random forest, neural networks, gradient boosting and support vector algorithms are notable subsets of machine learning algorithms, which have made significant contributions to several areas of public health, particularly in the forecasting of infectious diseases like malaria [87] and COVID-19 [88], and may have similar utility for making dengue outbreak predictions.…”
Section: Discussionmentioning
confidence: 99%
“…In the age of big data, this technique can leverage data availability and in addition to being non-parametric in nature, can also provide some leeway in terms of strict assumption. 72 Random forest, neural networks, gradient boosting and support vector algorithms are notable subsets of machine learning algorithms, which have made significant contributions to several areas of public health, particularly in the forecasting of infectious diseases like malaria 73 and COVID-19 74 , and may have similar utility for making dengue outbreak predictions.…”
Section: Discussionmentioning
confidence: 99%